FORMULATION AND IN-VITRO-IN-VIVO EVALUATION OF ALGINATE-CHITOSAN MICROSPHERES OF GLIPIZIDE BY IONIC GELATION METHOD - Sharma, Maya; Pk, Choudhury; Dev, Suresh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present work is aimed to formulate and evaluate alginate-chitosan microspheres of glipizide for the effective use in the treatment of diabetes. Methods: Sustained release microspheres were prepared by gentle mixing of polymers in water phase with drug by agitation. The polymers used for preparation were sodium alginate and chitosan, which was extruded into 5% calcium chloride solution to produce microspheres by ionic gelation method. Results: Single unit dosage form of Glipizide causes gastric irritation. To convert it in to the multiple unit dosage form will release the drug evenly throughout the stomach which suppresses the irritation. The aim of study towards formulation and evaluation of alginate-chitosan microspheres, which can provide sustained release of the model drug. It shows better in-vitro and in-vivo activity than conventional dosage forms. The work also aims to study various parameters affecting the behavior of microspheres in oral dosage form. Â Conclusion: Â Drugs that are simply absorbed from the gastrointestinal tract (GIT) and having a short half life are eliminated rapidly from the blood flow. To avoid this trouble, the oral sustained release (SR) has been developed as these will release the drug slowly in to the GIT and maintain a stable drug concentration in the serum for a longer period of time.